Improving elementary students’ HOTS and learning activeness through process skills–based problem-based learning - Wildah Afniar Nabila; Iin Hindun (Universitas Muhammadiyah Malang, 2025)
Most learning processes in Indonesian elementary schools still do not sufficiently foster higher-order thinking skills (HOTS) and active student participation. This classroom action research aimed to improve fourth-grade students’ HOTS and learning activeness in the IPAS (Science and Social Studies) subject through Problem-Based Learning (PBL) integrated with process skills. The study was conducted at SDN Beji 01 Batu (East Java) and involved 25 Grade IV-A students. The intervention was implemented in two cycles (planning, action, observation, reflection), each consisting of two meetings. HOTS were measured using a HOTS-oriented test, while student activeness was assessed through structured observation of process-skill behaviors. From Cycle 1 to Cycle 2, HOTS indicators improved substantially: analyzing (C4) increased from 42% to 81%, evaluating (C5) from 32% to 84%, and psychomotor naturalization (P5) from 44% to 92%. Students’ activeness also increased, with the overall average rising from 42.8% to 72.7%. These findings indicate that integrating PBL with process skills can effectively enhance elementary students’ HOTS and engagement, supporting the implementation of student-centered learning aligned with the Merdeka Curriculum.